Can MOOCs contribute towards enhancing disruptive pedagogic encounters in higher education - Waghid, Y.; Waghid, F. (South African Journal of Higher Education, 2017)
In this article, we argue that MOOCs (massive open online courses) have the potential to enhance disruptive pedagogic encounters in higher education, especially in relation to a philosophy of African education. In the first part of the article, we expound on MOOCs as an initiative in higher education that grew out of a concern to advance access to higher education. Paradoxically, we show that MOOCs might not strictly advance equal access and inclusion but have the potential to cultivate student capacities of a critically transformative kind, more specifically, rhizomatic thinking, criticism and recognition of others. In the second part of the article, we show, in reference to an emerging MOOC, how an African philosophy of education should be considered as apposite to advance disruptive pedagogic encounters in higher education.